(untitled) (Indian Journal of Animal Production and Management, 2024)
Present study was conducted to study the effect of extra concentrate supplementation with or without probiotics on milk composition and somatic cell count of goatsduring two months of periparturient period. Twenty four pregnant healthy Boar x local cross dose in the last month of gestation (day 120) were selected randomly and allotted to 4 groups (T1, T2, T3 and T4) of six animals. The dose were maintained under stall feeding conditions and offered a daily ration consisting of oats hay @ 1.2 kg/head/day and commercial pelleted feed @ 577.5 g/head/day. Dose in treatment groups T1 were offered normal daily ration without supplementation. In T2 group were offered normal ration and extra concentrate @ 150 gram /head/day, T3 group were offered normal ratio and extra concentrate @ 150 gram/head/day with probiotic (Saccharomyces cerevisiae x1010 CFU) @ 2.5 gram/head/day and in T4 groups were offered normal ratio and extra concentrate 150g + probiotic (Saccharomyces cerevisiae x1010 CFU) @ 4 gram/head/day. Milk samples were collected in the morning of 20th day of lactation and were analyzed for fat, protein, solid not-fat, total solids percent and somatic cell count using standard procedures. There was non-significant differences (p<0.05) infat, protein, solid-not-fatand total solids percent among different treatment groups. However, there was a significant difference (p<0.05) in SCC (103 /ml) of T3 and T4 group as compares to T1 (control) and T2 treatment group. Lowest SCC was found in T3 treatment group as 105.83±3.14 x103 /ml and highest in T1 (control) group as 128.66±0.80 x103 /ml.